Social determinants of hospitalizations for ambulatory care sensitive conditions in Guarulhos, São Paulo - Melo, Maykon Diego; Egry, Emiko Yoshikawa (Revista da Escola de Enfermagem da USP, 2014)
The study goals present an overview of Hospitalizations for Ambulatory Care Sensitive Conditions (ACSC) in Guarulhos, SP, from 2008 to 2012. This is an ecological study based on secondary data obtained from the Brazilian Hospital Information System, and supported by the Praxical Theory of Intervention of Collective Health Nursing. Applied descriptive statistics for analysis. It was observed that Guarulhos shows an upward trend in hospitalizations by ACSC (20% increase), the most frequent causes of heart failure (11.8%), cerebrovascular disease (10.6%) and angina (9.7%), most frequently in the age group ≥ 65years old, for both sexes. The results are similar to other Brazilian studies, but their analysis should extrapolate the biological limits and the supply of healthcare resources, focusing on the social determinants of the health-disease process.